Effect of Wobble Board Training with Mirror Feedback and Computer Based Balance Board Training on Static and Dynamic Balance and Quality of Life in Elderly Population (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The extent of the risk of falling rises with ageing, and the number of falls and accidents thatoccur strongly contributes to admission to a nursing home. Fall is mostly caused due to lack of balanceand also affect the quality of life, so the various Physiotherapy approaches are available for prevention andtreatment of fall but very few studies utilized computerized balance board training program to improve thebalance, hence need for the study is to find out the efficacy of balance board training & to enhancing balanceand gait as well as the significance of these training on static and dynamic stability and quality of life in thegeriatric population.Method: Total n=96 elderly people will be targeted who are about 60 years of age or older. Participants willbe randomly separated into two groups (control or experimental group).The training session design for a 6weeks and each session for a 20-30 minute. Outcome measures will be used to assess the static and dynamicstability and quality of life in the elder population group.Discussion: This clinical work seeks to equate the impact of traditional wobble board balance instructionin the elderly community and computer-based balance board preparation. To conclude, this work will helpelderly people strengthen their static and dynamic equilibrium, and also increase their quality of life.